Clinical significance of the abnormal Doppler spectrum of renal blood flow in patients with long-term transplant dysfunction - Yakymenko, V. V. (Zaporozhye Medical Journal, 2019)
Relevance. One of the main causes of graft loss in a recipient after kidney transplantation is acute rejection. The purpose of the work – to study the Doppler ultrasound measurements of renal transplant blood flow in patients with efficient depuration function and renal graft dysfunction in the late postoperative period following KT. Materials and methods. As an initial step, an ultrasound examination of renal transplants was performed in 26 patients with creatinine levels within the normative values (group 1) during the period 2014–2015. The second study was based on the ultrasound examination results of the renal transplants in 26 patients with creatinine levels exceeding the standard values (group 2) during the period 2015–2016. Results. The first group of recipients included 15 male (57.7 %) and 11 (42.3 %) female (the mean age was 31.40 ± 1.67 years). A living related kidney transplantation (LRKT) was performed in 61.54 % of patients, in 38.46 % – a cadaveric kidney transplantation (СKT). In all the patients, plasma creatinine level was within normative values or not exceeding them more than 25 %, on average, ranging from 94 to 130 µmol/L and its mean value was 114.5 ± 3.85 µmol/L. The second group of recipients consisted of 14 (53,84%) male and 12 (46,16%) female (the mean age was 38.99 ± 2.32 years). LRKT was performed in 6 patients, and СKT in 20 patients. In all the patients plasma creatinine level was above the normal range, on average, ranging from 155 to 629 µmol/L and its mean value was 259.46 ± 35,33 µmol/L. Conclusions. The obtained data reliably indicate that if TAMX of interlobar arteries less than 15 cm/s, the probability to reveal the clinical signs of renal allograft dysfunction is more than 90 %, regardless of the renal segment evaluation in recipients in the long-term period after organ transplantation.